(untitled) (Journal of Economic Research & Business Administration, 2015)
At the present stage of any economic study suggests a variety of activities at work, both theoretical articles, and with the results of empirical research. This complex combination of countervailing actions can cause the need to use effective tools for planning research, as well as tools for analyzing strengths, weaknesses of the proposed measures. It is therefore important to have a clear idea of the methods of organization and planning study for a positive result. Using technology allows critical analysis activities preparatory phase based upon a sufficient level. A scheme of the project will reflect the reality of its implementation and contribute to a more effective and a detailed implementation plan. This makes it possible at the design stage to avoid unnecessary economic and time-consuming.